Pengaruh Pemberian Pupuk Organik Cair Daun Lamtoro Dan Arang Sekam Padi Terhadap Hasil Produksi Tanaman Kedelai (Glycine max (L.) Merrill) - Purity Sabila Ajiningrum; Intan Permata Sari (FMIPA : Universitas PGRI Adi Buana, 2022)
Fertilization is one of the important activities in the maintenance of soybean plants to obtain optimal growth and production. Soybeans really need nutrients N, P, and K to meet the needs of growth, flower formation and pod filling. The research was to determine the effect of liquid organic fertilizer from lamtoro leaves with the addition of rice husk charcoal media on the yield of the number of pods and pod weight of soybean plants. There were 5 treatments, namely negative control (0%), positive control (inorganic fertilizers), A1 (10%), A2 (20%), A3 (30%) in increasing the growth of soybean plants. The study used CRD with 5 treatments and 5 replications. The statistical test used the ANOVA test and the LSD / LSD test, then the Duncan test was performed. The results of the study showed that the administration of POC of lamtoro leaves and rice husk charcoal had a significant effect (P <0.05) on the yield (number of pods and pod weight) of soybean plants with an optimal concentration of 30%. Keywords: rice husk charcoal, leaf of lamtoro, liquid organic fertilizer, soybean